Risk Assessment of Mud Cake on Shield Cutter Head Based on Modified Analytic Hierarchy Process - Wen Cao; Shoubao Xue; Yujia Xu; Huanyu Lin; Hui Li; Shengjun Deng; Lin Li; Yun Bai (Computation, 2025)
When the shield machines are constructed in soft soil, excavation may be impeded by the accumulation of cutter head mud. Geological conditions and shield construction are identified as the main factors for cutter head mud formation, based on analysis of its mechanism. In addition to traditional metrics, the imperforation area in the cutter head center is incorporated into the analysis of shield construction factors. The Analytic Hierarchy Process (AHP) is utilized to establish a risk assessment model for shield cutter head mud cake, determining the weight of each sub-factor and enabling a preliminary risk assessment of mud cake occurrence. This study applies Analytic Hierarchy Process (AHP) to classify the factors affecting shield mud by using the Mawan cross-sea channel construction project (Moon Bay Avenue along the Yangtze River) as a case study. Each factor is scored and weighted according to established scoring criteria and evaluation formulas, and then the results of the risk of shield mud cake in the Mawan tunnel are obtained. Moreover, field observations validate the proposed risk model, with the derived risk index demonstrating strong alignment with actual data.